Label‐free grading and staging of urothelial carcinoma through multimodal fibre‐probe spectroscopy. Issue 11 (13th August 2019) - Baria, Enrico; Morselli, Simone; Anand, Suresh; Fantechi, Riccardo; Nesi, Gabriella; Gacci, Mauro; Carini, Marco; Serni, Sergio; Cicchi, Riccardo; Pavone, Francesco S.
Abstract: Urothelial carcinoma (UC) is the most common bladder tumour. Proper treatment requires tumour resection for diagnosing its grade (aggressiveness) and stage (invasiveness). White‐light cystoscopy and histopathological examination are the gold standard procedures for clinical and histopathological diagnostics, respectively. However, cystoscopy is limited in terms of specificity, histology requires long tissue processing, both procedures rely on operator's experience. Multimodal optical spectroscopy can provide a powerful tool for detecting, staging and grading bladder tumours in a fast, reliable and label‐free modality. In this study, we collected fluorescence, Raman and reflectance spectra from 50 biopsies obtained from 32 patients undergoing transurethral resection of bladder tumour using a multimodal fibre‐probe. Principal component analysis allowed distinguishing normal from pathological tissues, as well as discriminating tumour stages and grades. Each individual spectroscopic technique provided high specificity and sensitivity in classifying all tissues; however, a multimodal approach resulted in a considerable increase in diagnostic accuracy (≥95%), which is of paramount importance for tumour grading and staging. The presented method offers the potential for being applied in cystoscopy and for providing an automated diagnosis of UC at the clinical level, with an improvement with respect to current state‐of‐the‐art procedures. Abstract : Fluorescence, Raman and reflectance spectra were collected from fresh biopsies of normal bladder and urothelial carcinoma (UC). A classification method based on principal component analysis was developed for discriminating normal from pathological tissues, as well as for distinguishing tumour stages and grades. Each individual spectroscopic technique provided high specificity and sensitivity in classifying all three categories. The presented method could be applied in cystoscopy and provide automated diagnosis of UC.